Accuracy Test of Qibla Direction of Qowiyuddin Mosque Jagir Wonokromo Surabaya - Anaam, Khairul; Isna Putri Sa’adah; Asri Arum Sari; Naurah Kamilah; Imroatul Mufidah; Nur Lailatul Qodriyahf (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2024)
This study was conducted to examine the accuracy of the Qibla direction of Masjid Qowiyuddin in Jagir Wonokromo, which is a crucial aspect of performing prayers (shalat) for Muslims. The instruments used in this research included the Mizwala Qibla Finder, Right-Angled Triangle, and Theodolite, each serving to ensure the precise measurement of the Qibla direction. Using a descriptive qualitative approach, the researcher collected primary data through interviews and direct field measurements, as well as secondary data from various literature references. The results showed a deviation in the Qibla direction by 23°49'12" to the north from the mosque’s current orientation, indicating the need for an immediate correction to ensure accurate alignment for worship. The urgency of this accuracy test is high, as the correct Qibla direction is a requirement for the validity of prayers. Therefore, it is recommended that the mosque’s management adjust the Qibla direction based on these findings and regularly verify its accuracy to avoid errors that could affect the quality of worship for the congregation.